(untitled) (Journal of Forest and Livelihood, 2003)
In line with government policy on decentralization, and recognizing the inadequacies of previous attempts for the management of Terai forests in Nepal, two donor funded programs are supporting localized planning and decision-making for the forest sector. To this end, District Forest Coordination Committees (DFCCs) are being established as permanent, multi-stakeholder forums in 11 Terai districts, involving Forest User Groups, government and non-government agencies, trade and industry, the media and political parties. Based on experiences over the past two years, this paper analyzes the prospects for DFCCs as permanent formal fora for collaboration among all district forest stakeholders. Using theoretical as well as practical insights, conditions that influence the effectiveness of multi-stakeholder platforms are discussed, including issues around legitimacy, representation, linkages between constituents and representatives, and coordination between and within levels. The author contends that the idea of DFCCs has great potential, but to ensure the success, a clear mandate and detailed guidelines are needed.